Treatment of TASC C and D Femoropoliteal Lesions with Paclitaxel eluting Stents: 12 month Results of the STELLA-PTX Registry. Issue 5 (November 2015) - Davaine, J.-M.; Querat, J.; Kaladji, A.; Guyomarch, B.; Chaillou, P.; Costargent, A.; Quillard, T.; Gouëffic, Y.
Abstract : Objective: The aim was to evaluate the safety and the efficacy of primary stenting with paclitaxel eluting stents for TASC C and D femoropopliteal lesions. Methods: Patients with TASC C/D de novo femoropopliteal lesions were treated by implanting paclitaxel eluting stents. Patients were included in a single center registry and prospectively followed by clinical and ultrasound evaluation. X-ray of the stented zone was systematically performed 12 months after implantation. The primary endpoint was primary sustained clinical improvement after 12 months. Results: A total of 45 patients (48 limbs) suffering from claudication (25 limbs) or CLI (23 limbs) were enrolled. Lesions were either TASC C (28 limbs) or TASC D (20 limbs). The mean length of the treated segment was 252 ± 90 mm. The mean number of stents was 2.9 ± 1 (2–5). Mean follow up was 12.7 months. No patient was lost to follow up. At 1 year post procedure, primary and secondary sustained clinical improvements were 56.3 ± 7.4% and 80.1 ± 5.9% respectively. Freedom from target lesion and target extremity revascularization were 63.6% and 90.1%, respectively. Primary and secondary patency rates were 52.5% and 79.6%. One year primary sustained clinical improvement rates for TASC C/D were 63.3 ± 9.2% and 45.6 ± 11.7%, respectively ( p = .34). One year primary sustained clinical improvement rates for claudication/CLI patients were 68 ± 9.3% and 41.6 ± 11.1%, respectively ( p = .13). The incidence of in stent re-stenosis and in stent thrombosis were 25% and 14%, respectively. The incidence of stent fracture was 12.5% on a limb basis and 9% on a per stent basis. Conclusions: The paclitaxel eluting stent did not achieve its goal in terms of prevention of in stent re-stenosis for TASC C/D femoropopliteal lesions. It requires frequent re-interventions during the first year to maintain satisfactory clinical results.